A Comprehensive Characterization of Simple Sequence Repeats in the Sequenced Trichoderma Genomes Provides Valuable Resources for Marker Development - Mahfooz, Sahil; Singh, Satyendra P.; Rakh, Ramraje; Bhattacharya, Arpita; Mishra, Nishtha; Singh, Poonam C.; Chauhan, Puneet S.; Nautiyal, Chandra S.; Mishra, Aradhana (Frontiers in Microbiology, 2016)
Members of genus Trichoderma are known worldwide for mycoparasitism. To gain a better insight into the organization and evolution of their genomes, we used an in-silico approach to compare the occurrence, relative abundance and density of SSRs in T.atroviride, T. harzianum, T. reesei, and T. virens. Our analysis revealed that in all the four genome sequences studied, the occurrence, relative abundance, and density of microsatellites varied and was not influenced by genome sizes. The relative abundance and density of SSRs positively correlated with the G+C content of their genomes. The maximum frequency of SSRs was observed in the smallest genome of T. reesei whereas it was least in second smallest genome of T. atroviride. Among different classes of repeats, the tri-nucleotide repeats were abundant in all the genomes and accounts for ~38%, whereas hexa-nuceotide repeats were the least (~10.2%). Further evaluation of the conservation of motifs in the transcript sequences shows a 49.5% conservation among all the motifs. In order to study polymorphism in Trichoderma isolates, 12 polymorphic SSR markers were developed. Of the 12 markers, 6 markers are from T. atroviride and remaining 6 belong to T. harzianum. SSR markers were found to be more polymorphic from T. atroviride with an average polymorphism information content value of 0.745 in comparison with T. harzianum (0.615). Twelve polymorphic markers obtained in this study clearly demonstrate the utility of newly developed SSR markers in establishing genetic relationships among different isolates of Trichoderma.